Impact of frailty, mild cognitive impairment and cognitive frailty on adverse health outcomes among community-dwelling older adults: A systematic review and meta-analysis - Chen, Baoyu; Wang, Mingting; He, Qin; Wang, Yong; Lai, Xiaoxing; Chen, Hongguang; Li, Mengqian (Frontiers in Medicine, 2022)
Aims: This study analyzes the impact of frailty, mild cognitive impairment, and cognitive frailty on adverse outcomes in community-dwelling older adults. Methods: This systematic review and meta-analysis were conducted using the PRISMA guidelines and MOOSE statement. We developed a specific search strategy for each electronic database and searched PubMed, Web of Science, MEDLINE, and Embase from initial records to July 2021. The studies on adverse outcomes of frailty, pre-frailty, mild cognitive impairment, and mild cognitive impairment with pre-frailty and cognitive frailty were included. Two researchers independently extracted data based on a spreadsheet and assessed the risk of bias. The primary outcomes were mortality, dementia, disability, and hospitalization. The second outcome included quality of life and falls. All analysis was conducted by using Review Manager (RevMan) 5.3 software. Results: A total of 22 cohort studies (71,544 older adults with mean age ranging from 65.1 to 93.6 years) were included with a low risk of bias and high methodological quality with a NOS score ≥7. Compared to robust elders, individuals identified as frailty were associated with a higher risk of mortality (RR = 2.11, 95% CI: 1.57-2.83) and disability (RR = 5.91, 95% CI: 2.37-14.74). Mild cognitive impairment with pre-frailty was associated with mortality (RR =1.74, 95% CI: 1.48-2.05) and dementia (RR =4.15, 95% CI: 1.87-9.20). Pre-frailty was associated with a higher risk of mortality (RR =1.29, 95% CI: 1.11-1.50). Cognitive frailty was associated with higher risk of incident mortality (RR=2.41, 95% CI: 1.97-2.94), dementia (RR = 3.67, 95% CI: 2.81-4.78), disability (RR=11.32, 95% CI: 4.14-30.97), and hospitalization (RR = 2.30, 95% CI: 1.60-3.32), as well as poor quality of life. Conclusion: Cognitive frailty could be a comprehensive psychosomatic predictor for adverse outcomes among older people. Interactions between frailty, mild cognitive impairment, and cognitive frailty on adverse outcomes must be further explored.